We are Egypt : the story behind the revolution - Paquette, Lillie; Lillie Paquette Productions; Soundview Media Partners ([United States] : [Lillie Paquette Productions], 2012)
Going beyond the headlines, this story, filmed in the fourteen months leading to the Revolution, highlights the years of mounting resentment against a U.S.-backed authoritarian government determined to stay in power at any cost. Embedded inside the turmoil, filmmaker Lillie Paquette followed key opposition figures and young democracy activists as they struggled against extraordinary odds and at great personal risk.
Originally released as a documentary in 2012.
Ayman Nour, Noam Chomsky, Anwar Sadat, Omar Sharif.
Narrator: Lillie Paquette.
Editors, Lillie Paquette, David Zlutnick.
Chiefly in English; portions in Arabic with optional English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed May 5, 2017).
Keywords: Egypt -- History -- Protests, 2011-; Egypt -- Politics and government -- 21st century; Democracy -- Egypt; Feature films; Documentary films; Nonfiction films; Internet videos; Streaming video